Implementation of IoT-Based Flood Emergency Application System (SADARI) for Real-Time Monitoring and Early Warning System in Dringu Probolinggo District - Afrikhatul Maulidiyah; Muhammad Imron Rosadi; Muhammad Faishol Amrulloh; Arief Andy Soebroto (Jurnal Teknologi, 2026)
Floods are hydrometeorological disasters that often occur in urban areas due to limited drainage capacity and high rainfall intensity. Delay in information on water conditions is one of the main factors in low preparedness for potential floods. This research aims to implement the Internet of Things (IoT)-based Flood Emergency Application System (SADARI) as a real-time monitoring and early warning system in Dringu District, Probolinggo Regency. The developed system integrates water level sensors and rainfall sensors, data loggers, and GSM-based communication modules for continuous data transmission. The research method uses a Research and Development (R&D) approach which includes the design, implementation, and testing stages of the system. The results of the implementation show that the system is able to monitor water levels in real-time and classify conditions into safe, alert, and hazard statuses. In field tests, the system successfully detected variations in water levels from normal (±16 cm) to dangerous conditions (±181 cm) and sent automatic notifications via Telegram Bot in a timely manner. In addition, the system is supported by an independent power supply so that it can operate sustainably in the field. Thus, the SADARI system can be an effective solution in supporting flood mitigation, improving community preparedness, and providing information on environmental conditions quickly and accurately.